Characteristics of the Fruits of Brazilian Species of Stylosanthes Sw. (Leguminosae) and Their Taxonomic Value - Silva Ferreira, Jamile Jorge da [UNESP]; Fortuna Perez, Ana Paula [UNESP]; Lewis, Gwilym Peter; Silva, Juliana Santos (Univ Chicago Press, 2021)
Premise of research. Stylosanthes, comprising approximately 50 species, is considered a taxonomically difficult genus, as its component taxa demonstrate very uniform external morphological characteristics. The presence of very similar species complexes within the genus is one of the principal factors complicating the identification of its taxa. Within that context, the present study seeks to morphologically analyze the fruit surface of Brazilian Stylosanthes species in a search for characteristics of potential use in the identification of species and species groups. Additionally, multivariate analyses (principal components analysis [PCA] and unweighted pair group method with arithmetic mean [UPGMA]) were used to elucidate patterns of variation within the species complexes and to test the validity of current species delimitations. Methodology. The fruits of 22 species of Stylosanthes were mounted, without previous treatment, directly on stubs using double-sided tape and were then sputter-coated with gold for examination using scanning electron microscopy (SEM). PCA and UPGMA were performed using 22 operational taxonomic units and 10 morphological fruit article characteristics. Pivotal results. The surfaces of the fruit articles are variously covered by simple trichomes, glandular trichomes, papillae, veins, and grooves. Four ornamentation patterns were observed, as follows: verrucose, papillose, reticulate, or reticulate with a papillose appearance. Multivariate analyses (PCA and UPGMA) do corroborate, in part, the three species complexes as traditionally circumscribed (the S. guianensis, S. macrocephala, and S. scabra complexes); however, accessions of S. guianensis species (S. guianensis complex) appeared nested within the S. macrocephala and S. scabra complexes. Conclusions. The micro- and macromorphological analyses provided results useful for separating species, as observed in the identification key, but multivariate analyses with only characteristics of fruit did not support the three traditional species complexes: S. guianensis, S. macrocephala, and S. scabra. Further multivariate analysis using other characters should be investigated to better understand the relationships of the species of each one of the complexes. But regardless of whether the complexes remained in this study, the results obtained from the fruit characteristics were useful in showing that it is important to separate the species treated here.
Keywords: Dalbergieae; microscopy; papillae; plant taxonomy